Analysis of dietary intake, diet cost and food group expenditure from a 24‐hour food record collected in a sample of Australian university students. Issue 2 (2nd February 2021) - McCartney, Danielle; Desbrow, Ben; Khalesi, Saman; Irwin, Christopher
Abstract: Aim: University students often cite increased monetary cost as a major barrier to improved eating behaviours. Here, we examine food expenditure behaviours in a sample of Australian university students. Methods: Students (n = 147) collected and analysed a 24‐hour food record to determine their food group and nutrient intakes, then costed the food and non‐tap water beverages consumed in the amounts recorded. Diet cost and food group expenditure (absolute and relative to total diet cost) were calculated and compared across socio‐demographic characteristics. Spearman's Rho correlations and partial correlations (controlling for energy intake) were also used to identify associations between diet cost and intake. Results: The median (IQR) 24‐hour diet cost was $12.42 ($7.06). However, students who worked ≥20 h·wk −1 had a higher diet cost than those who worked <20 h·wk −1 ( P = .002) or were unemployed ( P = .002). Relative food group expenditure also differed by sex, employment status and whether special dietary requirements were reported ( P' s < .05). For instance, males reported spending a smaller relative amount on the fruit and vegetables food groups and a larger relative amount on discretionary choices than females ( P' s < 0.05). Higher diet costs were also associated with greater intakes of the fruit, vegetables and lean meat and alternatives food groups, protein, alcohol, water and calcium, and lower intakes of the grain foods food group and carbohydrate ( P' s < .05). Conclusions: These findings provide insight into university students' food expenditure behaviours and may assist health professionals to develop targeted strategies and tailored advice aimed at improving their dietary behaviours.